KADAR HARA PADA PENAMBAHAN PUPUK KANDANG DAN SILIKA PADA TANAH SUPRESIF DAN KONDUSIF LAYU FUSARIUM PADA PISANG - Medina Uli Alba Somala; Sri Nuryani Hidayah Utami; Arif Wibowo; Siti Subandiyah (Plumula : Berkala Ilmiah Agroteknologi, 2018)
Fusarium wilt in bananas is caused by Fusarium oxysporum f.sp. cubense (Foc). Foc is one of the soil-borne pathogens. The intensity of disease attacks in different conditions with very severe is conducive soil. Suppressive soil can suppress and control the rate of development of soil-borne pathogens. The aims of this study are to determine the physical and chemical properties of soil and environment against fusarium wilt and find out the effects and levels of nutrients from the addition of manure and silica to fusarium banana wilt. Supressive soil samples from Sarampad, Cianjur and conducive soil from Salaman, Magelang. Ambon Kuning banana cultivar derived from tissue culture were planted to find out effects of manure and silica against fusarium wilt. Suppressive soil has higher soil chemist including neutral pH, sandy loam of texture class, total N, total P, organic C, organic matter, available Si than conducive soil. Manure and silica addition have significantly suppressed fusarium wilt on suppressive soil. The final experiment suppressive soil has higher total N, total K, organic C and organic matter than conducive soil.